2021
DOI: 10.3389/fimmu.2021.804895
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Extracellular Effector Vesicles From Human T And NK Cells: Same-Same, but Different?

Abstract: Cytotoxic T lymphocytes (CTL) and Natural Killer (NK) cells utilize an overlapping effector arsenal for the elimination of target cells. It was initially proposed that all cytotoxic effector proteins are stored in lysosome-related effector vesicles (LREV) termed “secretory lysosomes” as a common storage compartment and are only released into the immunological synapse formed between the effector and target cell. The analysis of enriched LREV, however, revealed an uneven distribution of individual effectors in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 129 publications
(195 reference statements)
0
16
0
Order By: Relevance
“…Although the timing and modes of activation and maturation are different, both CTL and Natural Killer cells (NK) utilize an overlapping arsenal consisting of cytotoxic effector proteins including FasL [ 102 ], perforins, granzymes and granulysin contained in their secretory lysosomes [ 78 , 144 ] (recently reviewed in [ 142 ]). The molecular mechanisms controlling the maturation and traffic of the secretory lysosomes and the polarized secretion of exosomes towards the synapse are, in great part, common to both cell types [ 44 , 102 , 145 ]. Thus, it is conceivable that approaches directed to increase exosome secretion in CTL ex vivo can also be useful to boost exosome secretion by CAR NK cells.…”
Section: Chimeric Antigen Receptor (Car) T Cells and Car T Cell-deriv...mentioning
confidence: 99%
“…Although the timing and modes of activation and maturation are different, both CTL and Natural Killer cells (NK) utilize an overlapping arsenal consisting of cytotoxic effector proteins including FasL [ 102 ], perforins, granzymes and granulysin contained in their secretory lysosomes [ 78 , 144 ] (recently reviewed in [ 142 ]). The molecular mechanisms controlling the maturation and traffic of the secretory lysosomes and the polarized secretion of exosomes towards the synapse are, in great part, common to both cell types [ 44 , 102 , 145 ]. Thus, it is conceivable that approaches directed to increase exosome secretion in CTL ex vivo can also be useful to boost exosome secretion by CAR NK cells.…”
Section: Chimeric Antigen Receptor (Car) T Cells and Car T Cell-deriv...mentioning
confidence: 99%
“…Therefore, expression of these death receptor ligands at the surface of NK cells is achieved by degranulation of LGs ( 66 , 70 ). In the case of FasL, several studies suggested that FasL is contained within distinct LG vesicles that do not contain cytotoxic proteins such as perforin and granzymes ( 18 , 71 73 ). In addition, it was also suggested that these LG subsets present different signaling requirements for degranulation and rely on distinct molecular processes for their secretion ( 18 , 74 ).…”
Section: Biogenesis Of Lytic Granulesmentioning
confidence: 99%
“…In the case of FasL, several studies suggested that FasL is contained within distinct LG vesicles that do not contain cytotoxic proteins such as perforin and granzymes ( 18 , 71 73 ). In addition, it was also suggested that these LG subsets present different signaling requirements for degranulation and rely on distinct molecular processes for their secretion ( 18 , 74 ). Future studies are required to better elucidate the identity and molecular regulation of FasL-containing vesicles, and it will be interesting to see whether TRAIL is also stored within the same (or a similar) subset of LG vesicles along with FasL.…”
Section: Biogenesis Of Lytic Granulesmentioning
confidence: 99%
See 2 more Smart Citations